Peripheral Vascular Dysfunction Following Spinal Cord Injury: A Systematic Review and Meta-Analysis. - Thordarson, Thomas; Miller, Tiev; Calderón-Juárez, Martín; Hosseinzadeh, Ali; Malik, Raza; Sachdeva, Rahul; Krassioukov, Andrei V. (Topics in Spinal Cord Injury Rehabilitation)
Spinal cord injury (SCI) has been shown to impact vascular function and increase the risk of cardiovascular disease (CVD). However, data are limited regarding prognostic factors for identifying subclinical CVD risk in individuals with SCI. To identify maladaptive structural and functional changes to central and peripheral vasculature resulting from SCI and to assess the effect of SCI on these parameters relative to able-bodied comparators. This review was prospectively registered. A systematic search was performed using PRISMA guidelines. Bias was assessed using the ROBINS-I and AHRQ tools. Studies reporting structural or functional changes to vasculature following SCI were included. Data on participant and injury characteristics, outcomes, and assessments used were extracted. Meta-analyses were conducted for adequately powered subgroups based on outcome type, measurement site, and level of injury. A total of 49 studies involving 1026 individuals with SCI and 941 able-bodied comparators were included. Most studies described injury level and severity using standardized impairment classifications. Subgroup analyses showed significantly reduced arterial diameter, compliance, endothelial function, blood flow volume, and high-density lipoprotein (HDL) cholesterol concentration among people with SCI compared to controls. Intima-media thickness, arterial stiffness, shear rate, and blood glucose and triglyceride concentrations were significantly greater for people with SCI compared to controls. Additional subgroup analyses were underpowered. This review synthesizes the current literature reporting central and peripheral vasculature outcomes in people with SCI and able-bodied controls. Between-group differences were observed for several structural and functional vascular outcomes, which suggests that SCI has a significant impact on multiple subclinical CVD risk factors.